1998
DOI: 10.1002/(sici)1097-0134(19980101)30:1<61::aid-prot6>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hydrophobic sites in proteins with xenon or krypton

Abstract: X-ray diffraction is used to study the binding of xenon and krypton to a variety of crystallised proteins: porcine pancreatic elastase; subtilisin Carlsberg from Bacillus licheniformis; cutinase from Fusarium solani; collagenase from Hypoderma lineatum; hen egg lysozyme, the lipoamide dehydrogenase domain from the outer membrane protein P64k from Neisseria meningitidis; urate-oxidase from Aspergillus flavus, mosquitocidal delta-endotoxin CytB from Bacillus thuringiensis and the ligand-binding domain of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
150
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 60 publications
11
150
2
Order By: Relevance
“…The use of noble gas pressurized crystallography is a way to characterize hydrophobic cavities 54 and in recent structures of Ngb under pressurized xenon 43, 44 , it was shown that the xenon atom in site II is lined by the five hydrophobic residues precisely forming the Ngb mechanical nucleus. Moreover, Xe still binds in this site when CO is bound and the heme has slid 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of noble gas pressurized crystallography is a way to characterize hydrophobic cavities 54 and in recent structures of Ngb under pressurized xenon 43, 44 , it was shown that the xenon atom in site II is lined by the five hydrophobic residues precisely forming the Ngb mechanical nucleus. Moreover, Xe still binds in this site when CO is bound and the heme has slid 43 .…”
Section: Discussionmentioning
confidence: 99%
“…[10] The promiscuous interactions of xenon with many proteins have also been investigated by the X-ray diffraction of protein crystals under high Xe pressure, where xenon can occupy hydrophobic cavities, substrate-binding sites, and also channel pores. [11] Notably, these are weak interactions, with hemoglobin and myoglobin exhibiting the highest reported xenon association constants of around 200 M −1 at rt. [12] In our search for a versatile genetically encoded reporter for Hyper-CEST NMR, we targeted a candidate protein TEM-1 β-lactamase (bla) based on its well-established allosteric site whose size and hydrophobicity suggest it to be a good target for Xe exchange.…”
mentioning
confidence: 99%
“…Variations of this approach involve, for example, the use of the heavy-metal clusters4, especially suitable for structures of very large macromolecular complexes, the gaseous xenon or krypton pressurized into native crystals5, or the short soaking in salts of halides6 (Br or I). It is also possible to obtain useful anomalous phasing signal from sulfur of Cys and Met naturally occurring in proteins789 or from phosphorus in nucleic acids10.…”
mentioning
confidence: 99%